On Two Projection Algorithms for the Multiple-Sets Split Feasibility Problem - Qiao-Li Dong; Songnian He (Journal of Applied Mathematics)
We present a projection algorithm which modifies the method proposed by Censor and Elfving (1994) and also introduce a self-adaptive algorithm for the multiple-sets split feasibility problem (MSFP). The global rates of convergence are firstly investigated and the sequences generated by two algorithms are proved to converge to a solution of the MSFP. The efficiency of the proposed algorithms is illustrated by some numerical tests.